Detection and molecular epidemiology of canine parvovirus type 2 (CPV-2) circulating in Jilin Province, Northeast China. (February 2021) - Jiang, Haoyan; Yu, Yue; Yang, Rui; Zhang, Shubo; Wang, Dan; Jiang, Yanlong; Yang, Wentao; Huang, Haibin; Shi, Chunwei; Ye, Liping; Yang, Guilian; Wang, Jianzhong; et al.
Highlights: CPV-2c has replaced the old genotypes and become the new major epidemic genotype in Jilin Province, Northeast China. Among 44 CPV-positive samples, 31 CPVs were typed as CPV-2c, 8 as new CPV-2a, 4 as new CPV-2b, and 1 as CPV-2. In the present study, the previously unreported VP2 Arg481Lys amino acid change was detected. Abstract: Canine parvovirus (CPV) is highly contagious and can cause haemorrhagic enteritis and myocarditis in dogs. To understand the current epidemic situation of CPV in Jilin Province, China, a total of 44 fecal or intestinal tissue samples of pet dogs suspected of being infected with CPV from February 2018 to November 2019 in Changchun and Liaoyuan City, Jilin Province were collected.All of the 44 collected samples were tested positive to CPV-2 by a PCR assay. The sequencing and analyzing of complete VP2 genes showed that CPV-2c was the most prevalent variant (n = 31;70.4 %), followed by new-CPV-2a (n = 8;18.2 %), new-CPV-2b (n = 4; 9.1 %) and CPV-2 (n = 1; 2.3 %). Phylogenetic analysis revealed that the 31 CPV-2c strains in our study are closely related to local CPV-2c isolates in cluster I. The VP2 protein of the acquired CPV 2c strains all possessed the substitutions Ala5Gly, Phe267Tyr, Tyr324Ile, and Gln370Arg only one with a novel Arg481Lys mutation. These findings demonstrate that CPV-2c was the most prominent type of CPV circulating in Jilin in 2018–2019, clustered in a separate group that is far from the vaccine strains and suggest that further and extensive epidemiological investigation among pet dogs are warranted to provide information for usage and research of current vaccines.